Um Barão e suas memórias em disputa: Grão Mogol (MG), Chapada Diamantina (BA) e Rio Claro (SP) - Parrela, Ivana Denise (2020)
This paper aims at analyzing the construction of different types of memory discourse on Grão Mogol Baron, Gualter Martins Pereira (1825-1890), in Grão Mogol (MG), Chapada Diamantina (BA) and Rio Claro (SP). In Grão Mogol, Martins Pereira is seen as agenerous politician responsible for important achievements. In the same vein, such perspective seems to be a widely held assumption in Chapada da Diamantina. However, in Rio Claro, he is regarded as a cruel coffee baron. In the present study the subjective nature of memory is taken into account (CANDAU, 2016). The way he is remembered over the years is continuously updated with little attempt to attain to reconstructing the past, but comprising new analysis frameworks (POLLAK, 1989). Another aspect that is worth noting has to do with memorial source use for analysis of historic actors’ trajectory, such as the baron, once the narratives are divergent and may not be encompassed in public policies for memory and cultural heritage intended to reconnect distant regions in the country.